Control interno de la Compañía Agrícola Calolasa del cantón Ventanas, período 2021. - Vera Galarza, Jimmy Marcelo (2022)
The study of internal control allows it to be defined, structured and implemented as an effective tool for safeguarding the company's resources. In this sense, this case study is developed around the internal control of the Compañía Agrícola Calolasa, with the objective of analyzing the company's internal control, determining the concepts related to internal control and their influence on management. of the company, in turn, based on this determination, diagnose the application of internal control and its components within the company for the subsequent evaluation of its implementation. For the optimal development of the case study and the fulfillment of its objectives, the COSO control model is defined, which is structured by five components that establish the foundations for the correct implementation of the control processes, generating a control environment that prioritizes the establishment of objectives and policies that direct internal control, determining evaluation mechanisms that contribute to the implementation of control activities that allow the correct progress of the objectives set and the protection of the company's resources, accompanied by information processes and communication that contribute to the adequate definition of the obligations related to the position, for an adequate development of the same, and that in turn contributes to the execution of supervision and monitoring mechanisms.